(untitled) (Research, Society and Development, 2021)
Nitazoxanide (NTZ) is a drug used in the treatment of viral and parasitic infections due to its mechanism of action to activate cell death processes. However, it has low oral bioavailability, restricting its use in therapy, with this, new delivery systems are necessary for better absorption in vivo. The objective of this narrative review was to address aspects related to the physicochemical characteristics of the Nitazoxanide molecule and its potential for repositioning. Searches were carried out in the Pubmed, Lilacs and Science Direct databases, selecting articles in English and Portuguese, crossing the descriptors "Nitazoxanida", "characterization" and "formulation" combined. Scientific evidence describes NTZ as a low molecular weight molecule, better absorbed at acidic pH, which undergoes deacetylation giving rise to its active metabolite, Tizoxanide. Studies report its application frequently in diseases by Giardia lamblia, Entamoeba histolytica and Cryptosporidium parvum, in addition to infections by protozoa, helminths, gram negative and positive bacteria and having antiviral properties, being related to its recent discovery in COVID-19, even associated with others drugs. Thus, systems such as liposomes, nanoparticles, microspheres, controlled-release tablets have been reported as vehicle enhancers in the release of the drug, in addition to enabling improvement in its physical-chemical aspects. Therefore, NTZ represents a molecule with great potential for application and repositioning, covering numerous possibilities.